Representasi Romantisme Remaja dalam Novel Dilan: Dia Adalah Dilanku Tahun 1991 Karya Pidi Baiq - Sahwa Laily (BADAN PENERBIT STIEPARI PRESS, 2025)
Representation is a description of something, someone, or an idea that is conveyed through written, visual, performance, or oral language. In literary works, language becomes the main tool for representation. This research aims to describe (1) a love story in the novel Dilan: Dia Adalah Dilanku Tahun 1991 by Pidi Baiq. (2) Expressions of love, sadness, disappointment, anxiety, regret and emotional reactions in the novel. The object in this research is the novel Dilan: He is my Dilan in 1991 by Pidi Baiq. This research is divided into two parts of the method, namely the approach and the type of research. The approach used is a qualitative descriptive approach using the theory of Literary Psychology. The results of the analysis in this study were only taken from a few quotes, focusing on the story, emotional reactions, and expressions of the characters. The conclusion in this research is that there is a unique romanticism in the novel, Dilan expresses his love for Milea in an unusual way, full of humor, and surprise, making their relationship feel colorful. This story depicts the sweetness of teenage love that is full of emotions, but also shows that maturity in making decisions is an important factor in a relationship.